1997
DOI: 10.1002/(sici)1097-4628(19970411)64:2<367::aid-app18>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Reaction catalyzed by montmorillonite: Polymerization of methyl methacrylate

Abstract: ABSTRACT:The polymerization of methyl methacrylate (MMA) was carried out in aqueous media having various concentrations of potassium persulfate as initiator in the presence or the absence of montmorillonite (Texas) at various temperatures. The rate of polymerization increased with increasing initiator concentration. Thermal stabilities of the resulting composite materials were studied and the activation energies of polymerization and degradation were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The increase in the polymerization rate could be attributed to the promotion of the clay on the chain initiation 4. This seemed to contradict the postponement of the polymerization, but a further inspection could eliminate this suspicion.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The increase in the polymerization rate could be attributed to the promotion of the clay on the chain initiation 4. This seemed to contradict the postponement of the polymerization, but a further inspection could eliminate this suspicion.…”
Section: Resultsmentioning
confidence: 98%
“…The E a values were determined to be 91.71 and 81.74 kJ mol −1 without and with clay, respectively, with the Arrhenius equation as follows: where R p is the initial polymerization rate at temperature T , A is the pre‐exponential factor, and R is the gas constant. The obvious reduction of E a was mainly due to the fact that the initiator and clay formed a complex4 that accelerated the chain initiation of the polymerization. Unfortunately, the mechanism is not clear and requires a thorough study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact can be explained by the catalytic effect of organo-MMT as a complexforming agent, which is similar to the well known effect of Lewis acids in complex-radical polymerizations [43]. Catalytic effect of organo-silicates in radical polymerization of vinyl and acrylic monomers have also been observed by many researchers [23,27,34,35]. In order to increase the effectivity of intercalation process and therefore, the formation of nano-structures in the studied system, MA and IA monomers were dispersed between silicate galleries before copolymerization reactions to prepare the fixed interlayer anhydride/alkyl amine (MA…DMDA-MMT) and carboxylic acid/alkyl amine (IA… DMDA-MMT through strong H-bonding) com- (Figure 3; here, well known lattice structural model of Hendricks for MMT was used [44]).…”
Section: Complex-radical Interlamellar Copolymerizationmentioning
confidence: 56%
“…Examples for interlamellar polymerization of the binary monomer systems are bulk copolymerization of styrenemethyl methacrylate [23,27,30], emulsion copolymerization of styrene-acrylonitrile [31], styrenephenyl maleimide (PhMI) [32] and styrene-butyl methacrylate [33] monomer pairs. It was observed that the polymerization rate was accelerated by the addition of the clay in reaction medium; this addition also significantly influenced the structure and properties of the prepared polymer nanocomposites [23,27,34]. Liu et al [35] investigated the bulk, solution and emulsion copolymerization of styrene with methyl methacrylate and N-phenylmaleimide (PhMI) (at 1:9 molar PhMI/styrene feed ratio) in the presence of organo(cetyltrimethyl ammonium bromide)-modified MMT or Na + -MMT in order to prepare nanocomposites with good dispersability of clay.…”
Section: Introductionmentioning
confidence: 99%